The Factors of the E-Commerce Growth during Covid-19 Pandemic: A Case Study of Shopee - editor aibpm; Zhisheng Wang; Shiying Wang; Saurabh Gavande; Wan Muhammad Zharfanuddin; Yifan Wang (Advances in Global Economics and Business Journal, 2022)
This study aims to investigate the factors of development and growth of Shopee revenue during the COVID-19 pandemic, the leading e-commerce online shopping platform in Southeast Asia and headquartered under Sea Group with advanced payment and logistical support. The research collected data from the company's official websites, customers' reviews, and questionnaires. For the survey respondent’s regions are focused on Malaysia. The findings provide sufficient evidence that the factors of Shopee growth during the pandemic related to the time background, matured online payment system, delivery system, and advanced business model.